Competition and Wholesale Electricity Market: the monitoring task assigned to the Peruvian electricity coordinator (COES) - Vargas Guevara, Erick (2020)
The aim of this work consists in studying the legal aspects of the monitoring task on the wholesale electricity market that Law 28832 and its regulations have assigned to the Economic Operation Committee of the National Interconnected Electric System of Peru (COES). Thus, we analyze the relevance of the competition surveillance in such a strategic and vital sector for every country as the electric is and the COES’ role as Peruvian government collaborator. Moreover, we describe the indicators usually used to measure the competition level within the electricity market and the ones approved by OSINERGMIN in 2017.Likewise, and considering the silence to this respect of the legislation’s statements of reasons and support reports, we answer why the monitoring function must fall to COES, concluding that it is justified in its closeness to the monitored agents. Precisely, this constant relationship between COES and electric agents allows the coordinator to access to relevant first-hand information for the competition indicators evaluation; ease that no governmental entity has.